2020
DOI: 10.1002/pen.25542
|View full text |Cite
|
Sign up to set email alerts
|

Chemical degradation and failure analyses by acoustic emission of PP/EOC blends exposed to ultraviolet radiation

Abstract: In this work, acoustic emission was used to investigate the effects of ultraviolet radiation on the mechanical behavior of blends of polypropylene (PP) with ethylene‐octene copolymer (EOC) containing photo stabilizers. Together with traditional techniques, like infrared spectroscopy and microscopy, the data obtained from acoustic emission helped the understanding of the failure caused by photodegradation and the influence of the stabilizing additives. Parameters like number and intensity of hits, released ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…16 A few dealt with PBT, such as on the evaluation of the effect of glass fiber 20,21 and the friction effect of PBT reinforced with glass microspheres on steel surfaces. 22 One of the current authors made some recent contribution on this theme, studying the failure of polypropylene by photodegradation, 17,18 and polyethylene terephthalate by stress cracking 19 with the use of AE as a tool.…”
Section: Introductionmentioning
confidence: 99%
“…16 A few dealt with PBT, such as on the evaluation of the effect of glass fiber 20,21 and the friction effect of PBT reinforced with glass microspheres on steel surfaces. 22 One of the current authors made some recent contribution on this theme, studying the failure of polypropylene by photodegradation, 17,18 and polyethylene terephthalate by stress cracking 19 with the use of AE as a tool.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with conventional elastomers, EOC has exhibited better compatibility with PP because of its long chain branches and the resultant low interfacial tension. [10][11][12][13][14][15] In the last decade, the PP/EOC blends have been studied in many different aspects, including as morphology development, rheological behavior, [16][17][18] mechanical properties, 19,20 and crystallization behavior. [21][22][23] Among others, the present research is focused on crystallization behavior because of its critical importance in polymer processing and mechanical behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Ethylene octene copolymer (EOC) has been highly regarded among ethylene α‐olefin copolymers derivatives. Compared with conventional elastomers, EOC has exhibited better compatibility with PP because of its long chain branches and the resultant low interfacial tension 10–15 . In the last decade, the PP/EOC blends have been studied in many different aspects, including as morphology development, rheological behavior, 16–18 mechanical properties, 19,20 and crystallization behavior 21–23 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] Although the AE technique is widely used to monitor crack propagation in metallic components, there are just a few studies in the literature that address polymer failure analysis using AE, and most of them are related to composite materials. [ 19 ] Some studies on the use of AE to investigate polymers were conducted by one the current authors on the effects of photodegradation [ 20,21 ] and stress cracking. [ 6 ] These studies were shown to be very helpful to a better understanding of product failure.…”
Section: Introductionmentioning
confidence: 99%